Selection for florfenicol resistance at sub-MIC concentrations in Pasteurella multocida - Abigail Hughes; Ludovic Pelligand; Dan I. Andersson; Andrew Mead (PLoS ONE, 2025)
Antimicrobial resistance is a global threat to both human and animal health, and transfer of resistance between these spheres is recognised as a key concern for all species. Selection for resistance at sub-inhibitory antimicrobial concentrations has been characterised for some bacteria-antimicrobial combinations but there is little data from non-laboratory strains, and veterinary antimicrobials and bacterial species. Here, we demonstrate a minimum selective concentration of 0.06 mg/L (1/6 xMIC) for florfenicol in wild-type Pasteurella multocida, through competition experiments between a susceptible strain and a floR-resistant mutant. We also show that sub-inhibitory concentrations of florfenicol do not appear to significantly select for de novo resistance in P. multocida and present the challenges with adapting experimental protocols between bacterial species. These results have important implications for antimicrobial resistance selection at sub-inhibitory concentrations, method development for within-species differentiation in novel bacterial species, and application to policy regarding antimicrobial contamination in animal-feed.